Land use in relation to composition and abundance of phlebotomines (Diptera: Psychodidae) in five foci of domiciliary transmission of cutaneous leishmaniasis in the Andean region of Colombia (2020)
American cutaneous leishmaniasis is a public health concern in Colombia, its incidence being sustained or focally increased principally by the emergence of domestic transmission concomitantly with the adaptation of the phlebotomine vectors to habitat transformation around households. The objective of the study is to scale up a rapid characterization methodology for evaluating the relationship of land use around the house to the composition and abundance of phlebotomines. Five sites with a history of domestic leishmaniasis transmission in the Andean area of Colombia were selected. The peri-domestic habitat was evaluated at 10 m intervals along eight radial transects, centered on each house, at 45° intervals using a web pattern. Phlebotomines were captured by placing three CDC light traps over two nights both indoors and outdoors (10 m from the house). Blood source and infection were determined by PCR. Spearman rank correlation coefficients and negative binomial regression were used to quantify associations between the phlebotomine abundance and habitat categories. The study demonstrated that the vectors were largely anthropophagic (62% of 79 were human blood) and that a single species in each site was favored by the pertaining agriculture monoculture. Specifically, Pintomyia (Pifanomyia) quasitownsendi was associated with sugar cane in Novillero and La Esmeralda; while Pi. (Pif.) longiflocosa was associated with coffee plantations in Agua Bonita and El Cucal. Honda Alta had a more diverse array of land use and forest coverage with a lower number of specimens but higher species diversity. In terms of distance from the house to an area of a given land use, the abundance of Pi. (Pif.) quasitownsendi was inversely related to the distance to sugar cane plantation (Spearman correlation coefficient, ? = -0.56, p < 0.001 for outdoor catches, and ? = -0.50, p < 0.001 indoors). A similar inverse relationship was observed for Pi. (Pif.) longiflocosa with regard to technified coffee (? = -0.51, p < 0.001 outdoors, and ? = -0.48, p < 0.001 indoors). This rapid characterization methodology could guide public heath decision makers in identifying those houses at higher risk of domestic transmission, and also educate farmers to increase the distance between their crops and any neighboring houses.